Why would some migrants choose to engage in degrading work? - Oded Stark; C. Simon Fan (University of Bonn, Center for Development Research (ZEF), 2011)
This paper develops a model of voluntary migration into degrading work. The essence of the model is a tension between two bads that which arises from being relatively deprived at home, and that which arises from engaging in humiliating work away from home. Balancing between these two bads can give rise to an explicit, voluntary choice to engage in humiliating work. The paper identifies conditions under which a migrant will choose to engage in degrading work rather than being forced into it, to work abroad as a prostitute, say, rather than on a farm. The paper delineates the possible equilibria and finds that greater relative deprivation will make it more likely that the equilibrium outcome will be engagement in prostitution. It is shown that under well specified conditions, every individual will work as a prostitute, yet every individual would be better off working on a farm. Put differently, when specific conditions are satisfied, there is a possibility of a coordination failure if individuals believe that everyone else will choose to be a prostitute, this belief will be self-fulfilling. In this case, all the individuals choose to engage in prostitution, which renders each of them worse off. The paper discusses various policy implications. It is shown that a policy intervention (a crackdown on migrants' engagement in prostitution), if implemented strictly, can increase everyone's welfare, but when the policy is implemented loosely, cracking down on prostitution will only reduce individuals' welfare without reducing their engagement in prostitution.
Keywords: F22; J24; J81; 330; Migrants; Relative deprivation; Degrading work; Humiliation; Multiple equilibria; Welfare assessment; Policy implications; Internationale Arbeitsmobilität; Prostitution; Migrationstheorie; Gleichgewicht; Wohlfahrtsanalyse; Theorie